Analisis Location Quotient dan Shift-Share Sub Sektor Pertanian Terhadap Potensi Pertumbuhan Ekonomi di Kabupaten Aceh Barat - Saswono, Hendri Adi; Mahrizal , Mahrizal; Arisna, Puput; Yasrizal, Yasrizal (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Economic growth in the current Era greatly affects the Development of a Region. Various sectors produced by a Region help drive the rate of economic growth and economic sub-sectors become one of the potentials that must be developed. Economic growth is an important phenomenon for the whole world including the Indonesian economy, one of which is the agricultural sector. In this study, the data used in this study is secondary data, where the data collected by researchers indirectly through other media intermediaries. While the data analysis technique used is based on analysis of Location Quotient (LQ) and Shift-Share Analysis. Thus, it can also be concluded that the Location Quotient (LQ) value of the agricultural sub-sector in West Aceh Regency during the 2019 - 2023 period shows that the highest value was achieved by the forestry and logging sector in 2019-2023 with a Location Quotient (LQ) of more than one indicating that the sector is a base sector. Conversely, the lowest value is in the Agriculture, Livestock, Hunting, and Agricultural Services sectors in 2019 - 2023 with a Location Quotient (LQ) of less than one indicating a non-base sector. The agricultural sector showed more moderate growth, with shift-share showing positive results, indicating that its growth rate was lower than the national average, but this sector still contributed to the regional economy where this sub-sector's advantages were the same as in other regions or all areas in Aceh province. Furthermore, forestry and logging showed more moderate growth showing positive results, indicating that its growth rate was lower than the national average, but this sector still contributed to the regional economy but this sector did not have advantages.